Problems and Solutions for Information Provision of Clusters by Small and Medium Enterprises (SMES) - Denchev, Emil (Research Papers, 2017)
The purpose of this study is to establish what is the level of information provision of the cluster, are there problems and need to improve it? The objectives of the study are to analyze the main characteristics of SMEs and clusters in Bulgaria, to conduct a survey of the information provision of the clusters, to analyze the results, to define the problems and to propose solutions. The methodology used is a survey method and methods of analysis and synthesis. Only clusters, members of the Association of Business Clusters (ABC) in Bulgaria, are interviewed. The proposed solutions allow consolidation of cluster-level information for cluster management purposes.
Keywords: Cluster; Traditional system; Good practices; ERP system; SQL queries